THE ROLE OF INTERNATIONAL RESEARCH IN THE DEVELOPMENT OF INTELLECTUAL ABILITIES IN PRIMARY SCHOOL MATHEMATICS EDUCATION - Baxronova Sarvinoz Akbar qizi (KONFERENSIYALAR, 2025)
Аnnotation.  This  article  analyzes  the  issue  of  developing  primary  school students' intellectual abilities through mathematics lessons. Based on international experience  and  research,  effective  approaches  in  this  area  are  discussed,  with particular focus on programs such as PISA, TIMSS, and CGI. The significance of methodological  approaches  that  support  intellectual  development  is  examined from a scientific perspective